2016
DOI: 10.1002/cbic.201600357
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot‐Based Nanotools for Bioimaging, Diagnostics, and Drug Delivery

Abstract: Quantum dots (QDs) are highly fluorescent nanocrystals with advanced photophysical and spectral properties: high brightness and stability against photobleaching accompanied by broad excitation and narrow emission spectra. Water-soluble QDs functionalized with biomolecules, such as proteins, peptides, antibodies, and drugs, are used for biomedical applications. The advantages of QD-based approaches to immuno-histochemical analysis, single-molecule tracking, and in vivo imaging (over traditional methods with org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
93
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(100 citation statements)
references
References 125 publications
1
93
0
1
Order By: Relevance
“…[7][8][9] The unique optical properties make QDs ideal probes for multiplexed analysisa nd multicolor imaging as QDs of severalc olors may be excited simultaneously with as ingle light source, and their emission peaks can be distinguished with ah igh resolution. [10,11] Moreover,t he multiplexed flow cytometry analysis with QD-encoded microbeads does not require complicated compensation procedures thus increasing the sensitivity of analysis. [4] Since 2001, when the concept of multicolor optical coding of microbeads with QDs was first suggested, [12] an umber of approaches has been designedf or engineering QD-encoded microparticles:e mbedding of QDs into the microbeads during the microbeads manufacturing, [13] incorporation of QDs into pores of swollenmicroparticles, [12,14] doping of mesoporous microbeads with QDs, [15] the concentration-controlled flow-focusing approach, [16] layer-by-layer deposition technique, [17] and encapsulation of QDs into polyelectrolytem icrocapsules.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The unique optical properties make QDs ideal probes for multiplexed analysisa nd multicolor imaging as QDs of severalc olors may be excited simultaneously with as ingle light source, and their emission peaks can be distinguished with ah igh resolution. [10,11] Moreover,t he multiplexed flow cytometry analysis with QD-encoded microbeads does not require complicated compensation procedures thus increasing the sensitivity of analysis. [4] Since 2001, when the concept of multicolor optical coding of microbeads with QDs was first suggested, [12] an umber of approaches has been designedf or engineering QD-encoded microparticles:e mbedding of QDs into the microbeads during the microbeads manufacturing, [13] incorporation of QDs into pores of swollenmicroparticles, [12,14] doping of mesoporous microbeads with QDs, [15] the concentration-controlled flow-focusing approach, [16] layer-by-layer deposition technique, [17] and encapsulation of QDs into polyelectrolytem icrocapsules.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 These unique properties make QDs ideal probes compared with traditional fluorescent dyes and they have been widely used for DNA sequencing, protein molecular detection, and cell and tissue imaging. [19][20][21][22][23] QDs have also demonstrated great power in multiplexed analysis because they can be simultaneously excited without overlapping emission peaks. Previous studies demonstrated that these characteristics can offer convenience in the multiplex detection of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor quantum dots (QDs) have emerged as alternative tools for cellular labelling, biochemical sensing, probing biocatalysed reactions, and drug delivery [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%